Investigating the complex relationship between movement competency scores, hip mobility, strength, and turnout measures in collegiate dancers - Pepin, M., E.; Prieur, V.; Skallerud, A. (Journal of Dance Medicine & Science, 2025)
Introduction: Turnout, or external rotation, is a fundamental movement pattern in dance and has been associated with injury risk. While previous research has examined the relationship between turnout and range of motion (ROM) while other contributing factors such as strength and movement competency have been largely overlooked. This study aimed to explore the relationships between functional turnout measurements and movement competency screen (MCS) scores, passive hip external rotation (PER) and external rotation strength in collegiate dancers. Understanding these relationships is crucial for optimizing training and reducing injury risk in dancers.